Corporal punishment in the Bible : a redemptive-movement hermeneutic for troubling texts - Webb, William J., 1957- (Downers Grove, Ill. : IVP Academic, 2011)
William Webb confronts those often-avoided biblical passages that call for the corporal punishment of children, slaves, and wrongdoers. How should we understand and apply those injunctions? Are we obligated to replicate them today? Building on the findings of his previous work in Slaves, Women & Homosexuals, Webb argues that a redemptive hermeneutic points us to God's ultimate ethic and enables us to remain truly biblical.
Biblical texts, ethical dilemmas and hermeneutical inconsistencies -- The slavery texts : a redemptive-movement model -- The rod and whip texts : a Biblical basis for going beyond -- What about adult corporal punishment? -- What about using only noncorporal methods for children? -- Conclusion : dare to read the Bible differently -- Postscript : an unplanned parenting journey -- Appendix : a response to Andreas Kastenberger.
Includes bibliographical references and indexes.
Keywords: Bible -- Hermeneutics; Corporal punishment -- Biblical teaching; Corporal punishment -- Religious aspects -- Christianity